Yeats's Poetic Codes. - Grene, Nicholas (OUP Oxford, 2008)
A new approach to Yeats's poems, concentrating on the reading experience itself. By picking out the distinctive 'codes' of Yeats's poetic practice, such as his use of dates and place names, characteristic vocabulary, and stylistic preferences, Grene's study will send readers back to the work with a new sense of understanding and enjoyment. - ;Nicholas Grene explores Yeats's poetic codes of practice, the key words and habits of speech that shape the reading experience of his poetry. Where previous studies have sought to decode his work, expounding its symbolic meanings by references to Yeats's.